2019
DOI: 10.12806/v18/i1/r6
|View full text |Cite
|
Sign up to set email alerts
|

Full-Range Leadership as a Predictor of Extra Effort in Online Higher Education: The Mediating Effect of Job Satisfaction

Abstract: Online higher education has rapidly expanded in the United States and displays a great opportunity for growth. Coupled with the growth of e-learning is the need for adjunct faculty to satisfy the need for additional online classes. Despite the importance of online adjunct faculty, little research has been performed to determine their work experiences. This quantitative, correlational study investigated the predictive relationship between the perceived use of transformational, transactional, and laissez-faire l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…The results are also in agreement with the findings of Barnett (2019), who focused on leadership styles and extra effort of the faculty. In the present study, the faculty took extra effort to learn technology and take online classes.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The results are also in agreement with the findings of Barnett (2019), who focused on leadership styles and extra effort of the faculty. In the present study, the faculty took extra effort to learn technology and take online classes.…”
supporting
confidence: 91%
“…The instructors also felt that conducting online classes during the protests may show the university in a bad light. Barnett (2019) conducted a study in a university in the United States to determine the relationship between transformational, transactional, and laissez-faire leadership behaviors and online teaching adjunct faculty's extra effort, as there is an increased demand for online courses from the students. The results showed that these leadership styles had a tremendous positive influence on the extra efforts of the adjunct faculty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The limitations on faculty agency inherent in the master course model have led some institutions to further devalue the role, substituting faculty-led courses for lower-paid, lesser recognized, and more easily inter-changeable instructor roles (Barnett, 2019). Such a path would be at odds with the culture of The Pennsylvania State University, but it does suggest the need for faculty development, i.e., for finding ways to support and treat even part-time instructors as valued and recognized members of the community of teaching and learning, even in conditions where they may not be able to meet in person.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the need for evaluative measures of instruction and instructor persists, perhaps even more so as trends point to a growing number of adjunct faculty teaching online courses for whom such measures can provide both accountability and professional development. (Barnett, 2019;Taylor, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Inspirational motivation is manifested in leaders who (a) articulate reasonable visions that inspire their followers to envision attractive future states, (b) challenge followers with high standards in enhancing performance, (c) communicate optimism about future goals, and (d) provide meaning to followers' works and arouse team spirit (Banks, et al, 2018 2019) identified that intellectual stimulation enabled leaders to improve the work environment and increase organizational creativity. Idealized influence, also known as charisma, provides the highest levels of ethical behavior and trust, where the leader becomes a role model to lead followers by example (Barnett, 2019;Guhr et al, 2019;Northouse, 2018). The idealized influence of transformational leaders is of increased importance to transforming employees' organizational performance.…”
Section: Literature 1 Concepts Of Leadership Stylesmentioning
confidence: 99%